Environmental Impact and Job Satisfaction on Employee Performance with Intervening Variables Work Motivation (Case Study: Refinery-Biodiesel Plant Division of PT. X) - Boy Andika Sinaga (Jurnal Indonesia Sosial Teknologi, 2024)
This research is intended to find out and analyse the impact of work environment and work satisfaction on employee performance, which is mediated by work motivation. The research was done quantitatively by using the survey method with data analysis technique using SEM PLS. The questionnaire was a data collection instrument and was spread online through Google Forms. It had a sample quota of 83 respondents from millennial-generation employees from a refinery-biodiesel plant in PT. X. The independent variable in this research is work environment (X1) and Job satisfaction (X2); the dependent variable is employee performance (Y) and, with mediating variable, namely work motivation (Z). The result from this research is that work environment (X1) and work satisfaction (X2) do not affect employee performance (Y) because the t-statistic values of 1,237 and 0,068 are successively lesser than 1,96 values with a significance of 0,05. With the mediation available in the form of work motivation (Y), it can be obtained data in which work environment (X1) and work satisfaction (X2) positively affect and signification to employee performance (Y) with t-statistic values by 2,157 and 3,872 successively with the significance lesser than 0,05. Besides that, work motivation (Y) also positively affects and is significant toward employee performance with a t-statistic value of 4,490 and a significance of 0,05. Further research is expected to research other variables that are able to support employees’ increasing performance, such as organisational commitment, work-life balance, and organisational culture.